Oxidative stress, inflammation, and markers of cardiovascular health. Issue 1 (November 2015) - Lakkur, Sindhu; Judd, Suzanne; Bostick, Roberd M.; McClellan, William; Flanders, W. Dana; Stevens, Victoria L.; Goodman, Michael
Abstract: Objective: To investigate associations of a oxidative balance score (OBS) with blood levels of total cholesterol, low-density lipoprotein- (LDL)-cholesterol, high-density lipoprotein- (HDL) cholesterol and triglycerides, and biomarkers of inflammation (serum C-reactive protein [CRP], albumin and venous total white blood cell [WBC] counts) among 19, 825 participants in a nationwide study. Methods: Using cross-sectional data 14 dietary and lifestyle components were incorporated into the OBS and the resulting score (range 3–26) was then divided into five equal intervals. Multivariable-adjusted odds ratios (ORs) for abnormal biomarker levels and 95% confidence intervals (CIs) were calculated using logistic regression models. Results: The ORs (95% CIs) comparing those in the highest relative to those in the lowest OBS equal interval categories were 0.50 (0.38–0.66) for CRP, 0.50 (0.36–0.71) for the total WBC count, and 0.75 (0.58–0.98) for LDL-cholesterol; all three p-values for trend were <0.001. The OBS-HDL-cholesterol association was statistically significantly inverse among females, but not among males. The OBS was not associated with serum albumin or triglycerides. Conclusion: Our findings suggest that an OBS may be associated with some, but not all, circulating lipids/lipoproteins and biomarkers of inflammation. Highlights: Associations of oxidative balance score (OBS) with lipids/lipoproteins and inflammatory biomarkers were investigated. High OBS indicates a presumably beneficial balance of pro- and anti-oxidants. For inflammatory biomarkers, OBS was inversely associated with high CRP and total WBC counts, but not low albumin. For lipids/lipoproteins, an inverse association was found with high LDL, total cholesterol, but not high triglycerides. Sex modified the association between OBS and low HDL.